Moses, Elijah, and Jesus’ Divine Glory (Mark 9.2–8) - Friedeman, Caleb T. ca. 20./21. Jh. (2024)
Scholars generally agree that Moses and Elijah appear at the Transfiguration because they are connected to each other in some way, and that this connection informs the significance of the story as a whole. However, there is no consensus regarding how Moses and Elijah are related, and consequently there is significant disagreement about how their presence contributes to the Transfiguration. The present study, which focuses on Mark's account (Mark 9.2-8), argues that Moses and Elijah appear together because they received similar theophanies at Mount Sinai and, as a result, the Transfiguration should be read as a mountaintop theophany in which Jesus constitutes the personal presence of Israel's God.
Keywords: Elijah; Moses; Mount Sinai; Transfiguration; divine Christology; Theophany